Assessment of Osteoprotegerin and Receptor Activator of Nf-Κb Ligand in Malaysian Male Patients with Chronic Obstructive Pulmonary Disease : A Cross-Sectional Study - Ahmad N., Bitar; Majed Ahmed, Al-Mansoub; Syed A., Syed-Sulaiman; Fadi G., Saqallah; Irfhan A.B, Hyder-Ali; Salah A., Alshehade; Amer, Hayat-Khan (Permanyer, 2024)
Background: Limited information exists regarding the pathophysiological interactions between osteoporosis and chronic obstructive pulmonary disease (COPD). Objective: To study the association of Osteoprotegerin (OPG) and receptor activator of nuclear factor kappa-Β ligand (RANKL) in male COPD patients. Methods: An observational clinical study was conducted at Penang General Hospital in Malaysia. Participants were divided into three groups: COPD patients with osteoporosis, COPD patients without osteoporosis, and healthy participants of the same age groups. Serum OPG (sOPG) and RANKL (sRANKL) levels were investigated. Results: The mean age of COPD patients was 64.10 ± 10.04 years. COPD patients had lower body mass index (23.22 ± 6.43) than healthy participants (27.32 ± 6.80). The T-score was significantly lower among COPD patients than healthy participants (p = 0.018). The sOPG concentration among healthy participants was significantly higher (361.90 ± 29.10 pg/mL, p < 0.001) than in the other groups, while the sRANKL concentration was not significantly different. The serum OPG/RANKL concentration was markedly higher in the control group than in the COPD patient group (p < 0.05). The COPD patients with osteoporosis had significantly lower pulmonary parameters (forced expiratory volume in the first [FEV]1% and FEV1/[forced vital capacity] (FVC), p < 0.01) and more dyspnea (modified medical research council = 2.60 ± 0.78 versus 1.90 ± 0.70, p < 0.01) than did the patients without osteoporosis. Furthermore, patients with severe COPD had a 3 times greater risk of developing osteoporosis (OR = 2.997 [95% CI = 2.181, 4.118], p < 0.001), while spirometric parameters had a significant inverse relationship with osteoporosis (FEV1% OR = 0.970, [95% CI = 0.954, 0.986], p = 0.001; FEV1/FVC OR = 0.984, (95% CI = 0.970, 0.999], p = 0.035). Conclusion: The study concluded that COPD patients had lower sOPG levels, leading to decreased OPG/RANKL ratio and faster bone resorption. Low bone mineral density was associated with more severe COPD. (REV INVEST CLIN. 2024;76(6):262-73)